Brief Announcement: Towards a Universal Approach for the Finite Departure Problem in Overlay Networks - Koutsopoulos, Andreas; Scheideler, Christian; Strothmann, Thim Frederik (Proceedings of the 27th ACM on Symposium on Parallelism in Algorithms and Architectures, SPAA 2015, Portland, OR, USA, June 13-15, 2015)

Structural Information and Communication Complexity - 22nd International Colloquium, SIROCCO 2015, Montserrat, Spain, July 14-16, 2015, Post-Proceedings

Einsatz additiver Fertigung zur Optimierung des Ermüdungsverhaltens von gekerbten Strukturen - Reschetnik, W.; Riemer, A.; Richard, H.A. (DVM - Tagung - Additiv gefertigte Bauteile und Strukturen, Deutscher Verband für Materialforschung und -prüfung e.V.)

Industrial applications in AM - aerospace and overhaul - Klemp, E. (ASME AM3D Conference and Expo)

Paradigmenwechsel mit Additiven Fertigungsverfahren - Möglichkeiten und Chancen - Klemp, E. (Generatives Fertigen und 3D-Drucken: Industrielle Revolution oder Hype? Wissenschaftliches Kolloquium)

Möglichkeiten, Chancen und Mythen additiver Fertigung - Klemp, E. (Hanse-Aerospace-Themennachmittag im Hause SLM)

Additive Manufacturing - Potenziale, Zukunftschancen und Hürden - Klemp, E. (Messe Interzum)

Technology Update 2015 for Metals - Klemp, E. (SLM-Usermeeting)

AM-Verfahren - Möglichkeiten in der industriellen Fertigung - Klemp, E. (VDMA - Symposium auf der Hannover Messe Industrie)

Mass finishing of laser sintered parts - Delfs, Patrick; Li, Z.; Schmid, Hans-Joachim (26th Annual International Solid Freeform Fabrication Symposium)

Temperature History within Laser Sintered Part Cakes and its Influence on Process Quality - Josupeit, Stefan; Schmid, Hans-Joachim (26th Annual International Solid Freeform Fabrication Symposium)
The temperature distribution and history within laser sintered part cakes is an important aspect regarding the process quality and reproducibility of the polymer laser sintering process. Especially the temperature history during the build and cooling phase is decisive for powder ageing effects and the development of part quality characteristics. In this work, a measurement system for three-dimensional in-process temperature measurements is set up and the influence of different parameters on the inner part cake temperature distribution and history is analyzed. Important factors are not only geometrical build job parameters like the part packing density and build height, but also process parameters like the layer thickness and bulk powder density. Individual in-process temperature profiles at different positions within a part cake are finally correlated with powder ageing effects. The results of this work help to understand the temperature history dependency of powder and part properties and can therefore be used to develop optimized process controls.

Material Properties of Laser Sintered Polyamide 12 as Function of Build Cycles Using Low Refresh Rates - Josupeit, Stefan; Lohn, Johannes; Hermann, E.; Gessler, Monika; Tenbrink, S.; Schmid, Hans-Joachim (26th Annual International Solid Freeform Fabrication Symposium)
Due to long process times at high temperatures, unmolten polyamide 12 material ages during the manufacturing process. Hence, it needs to be refreshed with new material for further build cycles. In application, refresh rates of about 50 % are commonly used. In this work, the recycling optimized material PA 2221 from EOS is analyzed along a series of 13 build and refresh cycles using a reduced refresh rate of 32 %. Before and after every build, the powder is analyzed regarding melt properties determined by MVR and DSC measurements. Thereby, in-process ageing effects are investigated and the steady-state conditions are determined accordingly. In addition, powder properties are directly linked to resulting mechanical and geometrical part properties. Key findings are a robust DSC measurement method for polyamide 12 powder, constant “circulated” material properties after three build/refresh cycles and robust tensile properties along the whole tested powder life cycle. As a result, process conditions of PA 2221 using reduced refresh rates can be derived from this work.

Surface roughness optimized alignment of parts for additive manufacturing processes - Delfs, Patrick; Toews, Marcel; Schmid, Hans-Joachim (26th Annual International Solid Freeform Fabrication Symposium)
The layered structure of Additive Manufacturing processes results in a stairstepping effect of the surface topographies. In general the impact of this effect strongly depends on the build angle of a surface, whereas the overall surface roughness is caused by the resolution of the specific AM process. The aim of this work is the prediction of the surface quality in dependence of the building orientation of a part. These results can finally be used to optimize the orientation to get a desired surface quality. As not every area of a part can be optimized, a predetermination of areas can be used to improve the surface quality of important areas. The model uses the digital STL format of a part as this is necessary for all AM machines to build it. Each triangle is assigned with a roughness value and by testing different orientations the best one can be found. This approach needs a database for the surface qualities. This must be done separately for each Additive Manufacturing process and is shown exemplary with a surface topography simulation for the laser sintering process.

Powder ageing and material properties of laser sintered polyamide 12 using low refresh rates - Josupeit, Stefan; Tutzschky, S.; Gessler, M.; Schmid, Hans-Joachim (Proceedings of the Rapid Tech 2015)
Powder ageing effects due to thermal load usually lead to a limited recyclability of unmolten polyamide 12 powders in the laser sintering process. In this work, the recycling optimized material PA 2221 is analyzed regarding its ageing behavior along a series of more than ten build/refresh cycles using a refresh ratio of about 30%. Thereby, the melt viscosity is measured before and after every cycle and the “steady-state” condition is determined accordingly. In addition, the material properties of parts manufactured with PA 2221 are discussed dependent on different process parameters and compared to parts made of standard PA 2200 material with a refresh rate of about 50%. These parameters include the mechanical properties as well as for example the impact strength and geometrical properties as function of layer thickness and testing temperature. As a result, the optimal process conditions and achievable material properties for PA 2221 can be derived from this work.

On design for Additive Manufacturing - evaluating geometrical limitations - dell'Aere, Guido; Zimmer, Detmar (Rapid Prototyping Journal)
Purpose – The purpose of this paper is to present Design Rules for additive manufacturing and a method for their development. Design/methodology/approach – First, a process-independent method for the development of Design Rules was worked out. Therefore, geometrical standard elements and attributes that characterize the elements’ shapes have been defined. Next, the standard elements have been manufactured with different attribute values with Laser Sintering, Laser Melting and Fused Deposition Modeling, and their geometrical quality was examined. From the results, Design Rules for additive manufacturing were derived and summarized in a catalogue. Findings – Due to the process independent method, Design Rules were developed that apply for the different considered additive manufacturing technologies equally. These Design Rules are completely function-independent and easily transferable to individual part designs. Research limitations/implications – The developed Design Rules can only apply for the considered boundary conditions. To extend the Design Rules’ validity, their applicability should be proven for other boundary conditions. Practical implications – The developed Design Rules practically support the design of technical parts. Additionally they can be used for training and teaching in the field of “design for additive manufacturing”. Originality/value – The developed Design Rules constitute a first step toward general Design Rules for Additive Manufacturing. Thus, they might form a suitable basis for further scientific approaches, and the Design Rules can be used to set up teaching documentations for lessons and seminars.

Entwicklung einer Methode zur systematischen Erarbeitung von Maßtoleranzen für additive Fertigungsverfahren - Lieneke, Tobias; Adam, Guido; Leuders, Stefan; Knoop, Frederick; Josupeit, Stefan; Delfs, Patrick; Funke, Nils; Zimmer, Detmar (Proceedings of the Rapid Tech 2015)

Systematical determination of tolerances for additive manufacturing by measuring linear dimensions - Lieneke, Tobias; Adam, Guido; Leuders, Stefan; Knoop, Frederick; Josupeit, Stefan; Delfs, Patrick; Funke, Nils; Zimmer, Detmar (26th Annual International Solid Freeform Fabrication Symposium)
Additive manufacturing offers many technical and economical benefits. In order to profit from these benefits, it is necessary to consider the manufacturing limits and restrictions. This applies in particular to the geometrical accuracy. Therefore, the achievable geometrical accuracy needs to be investigated, which enables the determination of realistic tolerances. Thus, two different aims are considered. The first aim is the determination of dimensional tolerances that can be stated if additive manufacturing is used under normal workshop conditions. Within the second aim, relevant process parameters and manufacturing influences will be optimized in order to reduce dimensional deviations. To achieve both aims a method was developed first. This method identifies relevant influential factors on the geometrical accuracy for the processes Fused Deposition Modeling (FDM), Laser Sintering (LS) and Laser Melting (LM). Factors were selected that are expected to affect the geometrical accuracy mainly. The first investigations deal with measuring linear dimensions on a designed test specimen and the derivation of achievable dimensional tolerances. This paper will present both, the developed method and the first results of the experimental investigations.

Systematische Erarbeitung von Konstruktionsregeln für die additiven Fertigungsverfahren Lasersintern, Laserschmelzen und Fused Deposition Modeling - Adam, Guido

On tolerances for additive manufacturing - Adam, Guido (Inside 3D Printing Conference and Expo)

Entwicklung einer Methode zur systematischen Erarbeitung von Maßtoleranzen für additive Fertigungsverfahren - Lieneke, Tobias (Rapid Tech 2015)